Let's Move with Leon. A randomised controlled trial of a UK digital intervention to improve physical activity in people with a musculoskeletal condition. (April 2023) - Webb, Justin; Stewart, Duncan
Abstract: Objective: This article presents a real-world evaluation of a digital intervention, 'Let's Move with Leon', designed to improve physical activity and health-related quality of life (HRQoL) in people with a musculoskeletal condition. Study design: A pragmatic randomised controlled trial. Methods: After randomisation and withdrawals were removed, 184 participants were assigned to receive the digital intervention with 185 assigned to a control group. Self-reported physical activity was the primary outcome. Health-related quality of life, the number of days completing strength-based exercises per week, the capability, opportunity, and motivation to be active, and step count were secondary outcomes. Outcomes were assessed over 4, 8 and 13 weeks. Results: Significant improvements were seen for self-reported physical activity at 13 weeks, reported strength days at 8 weeks, perceptions of physical capability and automatic motivation to be active at 4 and 8 weeks. No improvements were seen in step count or HRQoL over the control group. Conclusion: Digital interventions such as 'Let's Move with Leon' have the potential to increase physical activity in people with a musculoskeletal condition; however, improvements are likely to be small. Small improvements in physical activity may not be enough to improve HRQoL.